(untitled) (Perner’s Contacts, 2007)
The demands in regional bus public transport present problem, which caused the problems in area of public transport planning and determination the volume of service in public interest. For this reason it is necessary to determinated this PT demand with the help of methods which are able to to forecast and estimate the demands in space and time.